PERSEPSI DAN INTENSI PEKERJA MENJADI WHISTLEBLOWER DILINGKUNGAN KERJANYA: STUDI KASUS DI INDONESIA - Hezron Galio Sihombing (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2021)
This study aims to analyze the level of Perception and Intention of active workers to become whistleblowers in their work environment, will conduct a study of four forms of fraud, including: Bribery, Gratification, Extortion and Embezzlement that may occur around his work. In previous research, whistleblowing is the most effective way to detect fraud in the work environment. The population in this study is workers in various forms of organization but is limited only in Indonesia. Information about the perception of being a whistleblower, and its intentions. Primary data obtained through a questionnaire distributed to the samples sent. This research uses descriptive method that aims to present the answers of respondents to the questions asked. Is a description and clarification about an fenomena in the work environment. As for the results of the incoming questionnaire that ideally 100 percent of perceptions about the benefits of whistleblowing, there are 73 percent who agree. As for the ideal intention of 100 percent, it turns out 59 percent for bribes, 58 percent for gratuities, 62 percent for extortion and 65 percent for embezzlement. Key words: Whistleblower, Bribery, Gratification, Exhortion and Embezzlement